Precursor B-Cell Acute Lymphoblastic Leukemia/Lymphoma with L3 Morphology, Philadelphia Chromosome, MYC Gene Translocation, and Coexpression of TdT and Surface Light Chains: A Case Report - Alicia C. Hirzel; Aaron Cotrell; Robert Gasparini; Vathany Sriganeshan (Case Reports in Pathology)
Acute lymphoblastic leukemia is predominantly found in children. It is a neoplasm of precursor cells or lymphoblasts committed to either a B- or T-cell lineage. The immature cells in B-acute lymphoblastic leukemia/lymphoma can be small or medium sized with scant or moderate cytoplasm and typically express B-cell markers such as CD19, cytoplasmic CD79a, and TdT without surface light chains. These markers, along with cytogenetic studies, are vital to the diagnosis, classification, and treatment of these neoplasms. We present an unusual case of a precursor B-cell ALL, in an 82-year-old woman, who presented with pancytopenia and widespread lymphadenopathy. The cells show L3 morphology (Burkitt-like lymphoma) with coexpression of TdT and surface light chains in addition to an MYC gene translocation and Philadelphia chromosome.